Fabrication of Flexible Graphene Paper/MnO2 Composite Supercapacitor Electrode through Electrodeposition of MnO2 Nanoparticles on Graphene Paper. Issue 26 (12th July 2021) - Liu, Gu; Liu, Jian; Xu, Kejun; Wang, Liuying; Xiong, Shanxin
Abstract: The flexible electrodes are the crucial components for fabricating wearable supercapacitors. In this study, we present a quick and convenient method to prepare graphene paper (GP) as a flexible current collector on a large scale by an easy one‐step method. The composite electrode integrated with GP and MnO2 as a flexible supercapacitor was obtained by an electrochemical deposition method without using binder or conductive agent. The substrate (GP) of electrode not only provides mechanical strength, but also contributes energy storage capacity. The MnO2 nanoparticles deposited on the surface of GP further improved the electrochemical performance of composite. The neat GP can give a specific capacitance of 184 F/g at a current density of 1 A/g. At a current density of 1 A/g, the specific capacitance of the GP/MnO2 composite with a deposition time of 30 s is as high as 410 F/g. The method presented here shows great potential for the development of flexible electrode materials in practical energy storage devices. Abstract : A fast and simple one‐step reduction method was used to prepare flexible graphene paper with lightweight (0.2 g/cm 3 ) and high conductivity (16 Ω/sq) as the current collector. Then, by electrochemically depositing manganese dioxide on graphene paper, the composite electrode material shows good electrochemical performance (410 F/g) owing to the synergistic effect of rGO and MnO2 .